Experimental quantum advantage in the odd-cycle game - Drmota, P; Main, D; Ainley, EM; Agrawal, A; Araneda, G; Nadlinger, DP; Nichol, BC; Srinivas, R; Cabello, A; Lucas, DM (American Physical Society, 2025)
We report the first experimental demonstration of the odd-cycle game. We entangle two atoms separated by ∼ 2 m and the players use them to win the odd-cycle game with a probability ∼ 26σ above that allowed by the best classical strategy. The experiment implements the optimal quantum strategy, is free of loopholes, and achieves 97.8(3) % of the theoretical limit to the quantum winning probability. We perform the associated Bell test and measure a nonlocal content of 0.54(2) – the largest value for physically separate devices, free of the detection loophole, ever observed.